Comparative genomics reveals common diversity and adaptation to harsh environments in the Arabian Peninsula indigenous chickens - Assiri, A.; Vallejo-Trujillo, A.; Al-Abri, M.; Bahbahani, H.; Almathen, F.; Ahbara, A.; Al Marzooqi, W.; Tijjani, A.; Lawal, R.; Hanotte, Olivier H. (Wiley, 2025)
Identifying genomic regions under selection is crucial for comprehending the evolutionary history of the domestic chicken. Arabian Peninsula (AP) indigenous chickens are mostly found outdoors, being reared alongside other livestock for production purposes. These birds show high resilience to extreme temperatures (hot and cold), typical of the desert environment. The selection pressures responsible for unique local adaptations in these birds remain largely unidentified. Here, we aimed to investigate the genome diversity and structure of 15 indigenous chicken populations including 13 populations from the AP (n = 5), Ethiopia (n = 6), and the People's Republic of China (n = 2). We also included two commercial chicken populations, Fayoumi (selected for heat tolerance) and Chantecler (known for its cold tolerance). Principal component (PC) analysis separated all the populations based on their geographic areas of origin. PC1 separates the Ethiopian populations from the Chinese and AP populations, while PC2 separates the AP populations from the Chantecler, and the Ethiopian populations from the Dulong and Chantecler. The genome-wide signatures of analyses identified many candidate regions under positive selection. They include genes that may be associated with thermotolerance. These are involved in energy balance and metabolism (SUGCT, HECW1, MMADHC), cells apoptosis (APP, SRBD1, NTN1, PUF60, SLC26A8, DAP, SUGCT), angiogenesis (RYR2, LDB2, SOX5), skin protection to solar radiation (FZD10, BCO2, WNT5B, COL6A2, SIRT1) as well as growth (NELL1). Our findings suggest that Arabian chicken populations have a distinct gene pool polymorphism in relation to their adaptation to the harsh climatic environments of the AP.